Washback in language assessment - Green, Anthony (International Journal of English Studies, 2013)
This paper reviews the progress made in washback studies over the quarter century since Hughes’ (1989) placed it at the centre of his textbook Testing for Language Teachers. Research into washback and the development of models of washback are described and an agenda is suggested for test developers wishing to build washback into their programmes. It is recommended that future projects should pay greater attention to test design features and to the outcomes of learning as well as continuing to explore learner motivation and cultural factors that might encourage participants to react to tests in certain ways, but not in others. Washback research itself is seen to be a potentially valuable tool in persuading participants to adopt new practices.